Pediatric primary anaplastic ganglioglioma with malignantneuronal component - (:unkn) unknown (My University, 2018)
Gangliogliomas (GGs) represent approximately 0.4%-1.0% of all brain tumors.Anaplastic gangliogliomas (AGGs) form 5-10% of all GGs. They are a mixedneuronal-glial tumor of central nervous system and composed by two celllines; neuronal (ganglionic) and glial cells. Anaplastic component of AGGs isusually glial cells. Malignant neuronal component is a rare condition. Herewe report an 8-year-old male patient who was diagnosed with primary AGGwith malignant neuronal component and was treated with surgery, adjuvantradiotherapy and chemotherapy.